2010
DOI: 10.3168/jds.2009-2141
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Effect of sampling time relative to the first daily feeding on interpretation of serum fatty acid and β-hydroxybutyrate concentrations in dairy cattle

Abstract: Serum nonesterified fatty acid (NEFA) and beta-hydroxybutyrate (BHBA) concentrations are used to evaluate energy status in peripartum dairy cows. Blood samples from 37 cows in the week before parturition and 47 cows in the first week after parturition from 3 dairy herds were taken 1h before the first feeding (-1h) as well as 4 and 10h after the first feeding. Nonesterified fatty acid concentrations were measured in samples from cows before calving and BHBA was measured in samples from lactating cows. Mean NEFA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…, Table ) confirm the statement of Quiroz‐Rocha et al. () that these analytes are among the most commonly used energy‐metabolism‐related blood parameters to monitor EB. Greater NEFA concentrations post‐partum of cows overfed in the dry period corresponded to a more negative EB in those animals (Table ).…”
Section: Discussionsupporting
confidence: 82%
“…, Table ) confirm the statement of Quiroz‐Rocha et al. () that these analytes are among the most commonly used energy‐metabolism‐related blood parameters to monitor EB. Greater NEFA concentrations post‐partum of cows overfed in the dry period corresponded to a more negative EB in those animals (Table ).…”
Section: Discussionsupporting
confidence: 82%
“…For example, serum concentrations of glucose and insulin increase about 10% and 25% in cows at 3 h after grain feeding (Jenny and Polan, 1975). Non-esterified fatty acids in serum of cows 1 week before calving were shown to decrease from 0.20 mmol/l at 1 h before feeding to 0.14 mmol/l at 4 h after feeding (Quiroz-Rocha et al, 2010). In pigs, a decrease of free fatty acids in serum was seen within 1 h after feeding (Houpt et al, 1986), and insulin in plasma was found to increase postprandial (Koopmans et al, 2005).…”
Section: Animal-related Changesmentioning
confidence: 99%
“…Furthermore, several authors have reported effects of diurnal patterns (Andersson, 1988;Plaizier et al, 2005) or sampling time relative to feeding (Oetzel, 2004;Nikkhah et al, 2008;Quiroz-Rocha et al, 2010) on blood BHBA concentrations. The diurnal rhythm of BHBA was found to be associated with feeding frequency (Eicher et al, 1999).…”
Section: Introductionmentioning
confidence: 99%